2006
DOI: 10.1038/sj.bjc.6603065
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the metastasis-inducing protein AGR2 for outcome in hormonally treated breast cancer patients

Abstract: The anterior gradient protein-2 (AGR2) is inducible by oestrogen and itself can induce metastasis in a rat model for breast cancer. Here, a rabbit antibody to recombinant human AGR2 was used to assess its prognostic significance in a retrospective cohort of 351 breast cancer patients treated by adjuvant hormonal therapy. The antibody stains 66% of breast carcinomas to varying degrees. The percentage of positive carcinoma cells in tumours directly correlates with the level of AGR2 mRNA (Spearman's rank correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 22 publications
6
78
3
1
Order By: Relevance
“…Our in vitro data predict an involvement of AGR2 in response to tamoxifen-based therapy and initiated our evaluation of AGR2 expression in clinical samples from patients with primary breast carcinoma and from secondary tumours developed during tamoxifen treatment, where we found significantly higher levels of AGR2 in tumours exposed to tamoxifen (Figure 7a). Our findings contradict speculations that the anti-estrogenic effects of tamoxifen would suppress the expression of AGR2 as a negative prognostic factor (Innes et al, 2006). This presumption was based only on the observation that expression of AGR2 is downstream of ER and is present at much higher levels in estrogen-responsive MCF-7 cells in the presence of estrogen (Liu et al, 2005).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Our in vitro data predict an involvement of AGR2 in response to tamoxifen-based therapy and initiated our evaluation of AGR2 expression in clinical samples from patients with primary breast carcinoma and from secondary tumours developed during tamoxifen treatment, where we found significantly higher levels of AGR2 in tumours exposed to tamoxifen (Figure 7a). Our findings contradict speculations that the anti-estrogenic effects of tamoxifen would suppress the expression of AGR2 as a negative prognostic factor (Innes et al, 2006). This presumption was based only on the observation that expression of AGR2 is downstream of ER and is present at much higher levels in estrogen-responsive MCF-7 cells in the presence of estrogen (Liu et al, 2005).…”
Section: Discussioncontrasting
confidence: 89%
“…Strikingly, AGR2 was identified as the first protein able to promote cell migration and regeneration in severed nerves, which normally provide signal to stimulate regeneration (Kumar et al, 2007). Clinical studies have also implicated the protein in inflammatory bowel disease (Zheng et al, 2006), hormone-dependent breast cancers (Thompson and Weigel, 1998;Fletcher et al, 2003;Innes et al, 2006), and a range of non-hormone cancers (Lee et al, 2006;Zhu et al, 2007). Furthermore, AGR2 predicts poor prognosis in prostate cancers (Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similar controversy regarding the prognostic value of AGR2 expression has been observed in breast cancer; with AGR2 upregulation associated with favorable prognosis in one study, 37 and with poor prognosis in another independent analysis. 11 Previous studies of PDAC did not identify a correlation between AGR2 expression and prognosis. 15 Our univariate analysis revealed that AGR2 downregulation correlated with poor prognosis in PDAC patients.…”
Section: Discussionmentioning
confidence: 94%
“…9 Several studies have shown that AGR2 is overexpressed and promoted tumor progression in numerous human malignancies affecting the ovary, breast, lung, prostate, and pancreas. [10][11][12][13][14] In PDAC, Ramanchandran et al 14 reported that AGR2 expression was elevated, even in PanIN1A, the earliest precursor lesion of PDAC. In this context, AGR2 promotes cancer cell proliferation, invasion, and resistance to chemotherapy, suggesting that AGR2 promotes cancer progression; however, the mechanisms underlying AGR2 function in advanced PDAC remain unclear.…”
mentioning
confidence: 99%